The impact of branding on the efficiency of the process of attracting and retaining talented employees - Sančanin Branislav (Trendovi u Poslovanju)
A company's reputation can be crucial in attracting and retaining talented employees. And brand's relevancy is a synthesis of all the efforts put towards an employee and potential candidates who then interpret this is a good working place. The importance of branding is high as it strengthens competitive advantage, and its relevancy is also seen during the process of attracting and retaining talented employees to a company promoted as a desired working place. As a response to numerous challenges on the job market, companies tend to compete in branding strategies - from dedicated branding to broad corporative branding. Despite the fact that communication made on social media, with the goal to build a positive image and reputation, is less susceptible to control than traditional media, the process of creating a positive perception of the brand leads to companies using mediums which enable a real and interactive contact with target audience. Numerous research show that posting information on social media, as available, frequent and cheap communication channels, establishes a two-way communication and ensures there is feedback.